Analysis of impact of frontline demonstrations on adoption of improved technologies of oilseed crops: ANALYSIS OF OILSEED FRONTLINE DEMONSTRATIONS ON ADOPTION OF IMPROVED TECHNOLOGIES - GARIKAMUKKALA ASHA LATHA SRI; G D S KUMAR; M A KHAN (Journal of Oilseeds Research, 2023)
The major objective of frontline demonstrations (FLDs) is to demonstrate the productivity potential and profitability of improved technologies in farmers’ fields. It is based on the principles of learning by doing and seeing is believing. It is assumed that the demonstrations will aid in increasing the adoption of improved technologies by the farmers and result in reducing the yield gaps at field level. The present study was conducted during the year 2021-22 in eight villages of the Prakasam and Raipur districts of Andhra Pradesh and Chhattisgarh states, respectively with the objective to assess the impact of FLDs in terms of adoption of improved technologies by FLD and non-FLD farmers. The data were collected from a total of 160 FLD and non-FLDs farmers cultivating oilseed crops. Adoption index was estimated and it was found that FLD farmers had high adoption index as compared to non-FLD farmers indicating higher adoption levels among FLD farmers.